The role of the Institute for Missiological and Ecumenical Research in the past and present - Van Niekerk, A. S. (Verbum et ecclesia, 2009)
IMER, the Institute for Missiological and Ecumenical Research, was initiated in 1979, when the 20th century missionary movement in the Dutch Reformed Church had already started to unravel. IMER’s history gives us insight into these events. IMER has focused on the missionary calling of the church and on guiding the church in its broad responsibility to Southern African society. IMER conducted a comprehensive study on the unfinished task in the eighties, from which a variety of other projects followed. The understanding of the task of mission has gradually broadened to include the church’s responsibility to the whole of life, with faith in Christ at the centre. However, as funding for the missionary movement diminished and the university had to cut down on expenses, funding for IMER dried up. IMER is now in the same position as mission itself, and even many congregations: it has to be innovative and find new structures and new sources of funding to respond to the challenges of a new century.